Aproximación a la valoración del know how de una institución del sistema regional de innovación en Antioquia. (2015)
In regional innovation systems, the need has been sharpened to value intangible assets, especially the know how to negotiation and commercial transfer. Therefore, the aim of the article is to identify the main methods of valuing intangibles and deploy an implementation in an institution dedicated to the incubation of new businesses. In terms of methodology, the documentary analysis is combined with the cost method, which consists of collecting the underlying costs for the development of know how. Regarding the results, it was found that for these institutions it is easier and more appropriate to apply the cost method, which allowed estimating the unit cost per transfer.